Source Studies Potential of 20th-Century Epitaphs (based on the example of epigraphic monuments in the village of Zildyarovo in the Miyakinsky District, Republic of Bashkortostan) - Nurida Sh. Nasibullina; Regina B. Mirzayanova; Aigul I. Akhmetova (Археология евразийских степей, 2025)
Gravestone, regardless of the time of their creation or the skill level of the carver, serve as a unique source of information for history, linguistics, ethnography, ethnology, codicology, religious studies, and other academic disciplines. This article presents the preliminary results of epigraphic research conducted in one of the settlements of the former Belebey Uyezd – the village of Zildyarovo in the Miyakinsky district, the Republic of Bashkortostan. The materials included in this publication are purely source-based in nature and are being introduced into scholarly discourse for the first time. Each epitaph is accompanied by a detailed description of the monument's external features, including the most comprehensive interpretation of its content possible at this stage of research. Texts written in Arabic script are supplemented with translations into modern Russian, enabling the research findings to be used not only for further studies in reconstructing the historical data of the settlement but also to fill gaps in dialectology and other fields.